1965
DOI: 10.1111/j.1365-2621.1965.tb01881.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing Agents on the Growth and Survival of Food‐Poisoning Strains of Clostridium perfringens

Abstract: SUMMARY The effects of different combinations of curing salts (NaCl, NaNO3, NaNO2) and temperature on the growth, survival, and heat resistance of several strains of Clostridium perfringens were investigated. These strains were shown to survive and grow in concentrations of curing salts considerably higher than those used in normal curing operations. When used in conjunction with heat, the concentrations of curing salts required to affect cell survival were still well above those usually employed. Hams were pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Pivnick et al (1 970) concluded that the main value of nitrite in stabilizing canned, cured shelf-stable meats appears to reside in its ability to aid in the prevention of growth from spores that survive heat processing and germin a t e during post-processing storage. Gough and Alford (1965) found several strains of Clostridium perjringens survive and grow in concentrations of curing salts considerably higher than those used in normal curing operations. The greater numbers of aerobic and anaerobic bacteria in meats premixed with nitrite alone or in combination with isoascorbate than in meats mixed only with salt were not readily explained.…”
Section: Influence Of Curing Saltsmentioning
confidence: 99%
“…Pivnick et al (1 970) concluded that the main value of nitrite in stabilizing canned, cured shelf-stable meats appears to reside in its ability to aid in the prevention of growth from spores that survive heat processing and germin a t e during post-processing storage. Gough and Alford (1965) found several strains of Clostridium perjringens survive and grow in concentrations of curing salts considerably higher than those used in normal curing operations. The greater numbers of aerobic and anaerobic bacteria in meats premixed with nitrite alone or in combination with isoascorbate than in meats mixed only with salt were not readily explained.…”
Section: Influence Of Curing Saltsmentioning
confidence: 99%
“…The presence of curing salts inhibited the growth of C. perfringens at the temperatures at which growth occurred rapidly in noncured ground pork (44.4 to 36.3uC) and delayed growth between 36.3 and 24.2uC. The inhibitory effect of curing salt has been reported previously (1,14,19,20,23,38). However, under the cooling conditions tested (chilling from 54.4 to 7.2uC for 20 h), the initial population of 3 log CFU/g decreased to 1.9 log CFU/ g in the first 4 h of cooling, and from this point the C. perfringens population increased to 2.8 to 3.4 log CFU/g after 17 to 20 h of cooling (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…The inhibitory action of sodium nitrite on the growth of clostridia in both bacteriological media and meat has been studied extensively (4,8,9,11,18), but the mechanism of inhibition is not known. Riha and Solberg (10) have characterized the growth of Clostridium perfringens in a chemically defined microbiological medium.…”
mentioning
confidence: 99%